2018
DOI: 10.1093/ntr/nty054
|View full text |Cite
|
Sign up to set email alerts
|

Are Electronic Cigarettes an Effective Aid to Smoking Cessation or Reduction Among Vulnerable Groups? A Systematic Review of Quantitative and Qualitative Evidence

Abstract: Smoking prevalence among people with mental illness, substance misuse, homelessness or criminal justice system involvement remains high. E-cigarettes could support cessation. This systematic review found limited quantitative evidence assessing effectiveness. No serious adverse events were identified. Qualitative thematic synthesis revealed barriers and facilitators mapping to each component of the COM-B (capability, opportunity, motivation, behaviour) model, including practical barriers; perceived effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 49 publications
1
34
0
1
Order By: Relevance
“…The evidence base on MRP is expanding exponentially, and it is clear that, despite ongoing efforts at regulating their use (e.g., with increased taxation), MRP usage will continue to grow [ 3 , 8 , 9 , 34 ]. Accordingly, it is paramount to expand the evidence concerning these products, with details worth being sought ranging from cardiovascular effects to additivity and polluting impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence base on MRP is expanding exponentially, and it is clear that, despite ongoing efforts at regulating their use (e.g., with increased taxation), MRP usage will continue to grow [ 3 , 8 , 9 , 34 ]. Accordingly, it is paramount to expand the evidence concerning these products, with details worth being sought ranging from cardiovascular effects to additivity and polluting impact.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the use of HNBC has rapidly increased worldwide, particularly among young individuals [ 7 ]. Whether these novel modified risk products (MRP) may actually prove as reduced risk products (RRP) remains still uncertain, despite several reports suggesting that both EVC and HNBC may prove less detrimental than TCC in several dimensions [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an ongoing trial is examining the effectiveness and side effects of combining varenicline with e-cigarettes for smoking cessation among those with mental disorders 39. Recent reviews on the use of e-cigarettes for cessation among vulnerable groups concluded there is insufficient evidence to determine effectiveness 40 41. Findings have also demonstrated the relevance of contextual factors, including physical and social environment, as important barriers to address in smoking cessation efforts 42 43.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vulnerable populations with high smoking rates may perceive ENDS more favourably than prescription pharmacotherapy and, because ENDS avoid the ‘barrier’ of requiring a prescription, may be more easily obtained and used. However, a systematic review found the evidence to be weak to moderate, limiting any conclusions . The motivating reasons why people use ENDS may provide insight as to likely outcomes; for example, only 39% of Australian smokers cite smoking cessation as a motivation for using ENDS, as opposed to 65% of smokers who use NRT patches .…”
Section: Do Ends Help People Quit Smoking?mentioning
confidence: 99%